Incorporation of risk preferences in a value‐based systems engineering framework. Issue 2 (15th January 2020) - Kannan, Hanumanthrao; Mesmer, Bryan L.; Bloebaum, Christina L.
Abstract: Large‐scale complex engineered systems are designed in large organizations consisting of hundreds or thousands of individuals making design decisions at different stages in the process. These complex systems are inherently multidisciplinary and uncertain, involving diverse disciplines spanning geographical locations. Without a means to guide their decisions, these many decision‐makers fall back on selecting a design according to their own value and risk preferences. The primary focus of this paper is to enable consistency in design decision‐making with respect to both value and risk preferences of the stakeholder. A new value‐based systems engineering (VBSE) framework is presented that enables physics‐based system consistency as well as consistency in communication of value and risk preferences for design decision‐making in a hierarchically decomposed system. This framework embraces principles of value‐driven design and multidisciplinary design optimization, while also ensuring consistency in risk preferences throughout the system to address uncertainty. Improper communication of risk preferences could result in nonoptimal designs, which are risk biased by the design decision‐makers at different levels of the hierarchy, with respect to the stakeholder's preferences. Consistency in risk preferences in the context of the VBSE framework is addressed in this research by incorporating decision analysis techniques.